Minimally Invasive Technique for Spontaneous Intraparenchymal Hemorrhage - Himanshu Raval; Kalpesh Shah; Mona Bhatt (Indian Journal of Neurosurgery)
Objective The aim of this study was to introduce a cost-effective and less invasive method for the evacuation of intraparenchymal hemorrhage (IPH).